Thematic Textbook Based on Local Wisdom - Wina Nurfitriani; Sumarmi Sumarmi; Hariyono Hariyono (Jurnal Pendidikan Humaniora, 2018)
Abstract: Local wisdom based education is a part of the implementation of character building principles in education which enable students to prepare themselves for future. The local wisdom plays significant role since the implementation of real life context in teaching learning activities is the best approach to initiate the lesson. Not only as a basis in teaching learning activity, the implementation of local wisdom will assist student to comprehend every concept in learning material, therefore students will be able to implement their cognitive ability in daily life. One of means of integrating local wisdom is by transferring it to the textbook. Research and development study need to be done in developing local wisdom based textbook. The aim of research and development study is to create a valid, interesting, practical and effective textbook. Thiagarajan’s 4D model was implemented in this research and development study. The data analysis shows that this book is valid, interesting, practical and effective to use in teaching learning process.Key Words: textbook development, local wisdomAbstrak: Pendidikan berbasis nilai-nilai kearifan lokal adalah pendidikan yang menerapkan prinsip-prinsip pembentukan karakter. Kearifan lokal sangat penting karena terkait dengan penyiapan kualitas generasi yang akan datang. Proses pembelajaran haruslah dimulai dari lingkungan terdekat atau yang sering dijumpai siswa. Nilai-nilai kearifan lokal dapat membantu siswa memahami konsep nilai-nilai positif dalam materi buku teks. Kearifan lokal dijadikan basis dalam pengembangan buku teks tematik di sekolah dasar. Penelitian dan pengembangan ini bertujuan untuk mengembangkan buku teks tematik berbasis kearifan lokal yang valid, menarik, praktis, dan efektif. Model penelitian dan pengembangan dilakukan dengan menggunakan model 4D dari Thiagarajan. Hasil analisis data menunjukkan bahwa buku teks yang dikembangkan telah memenuhi kriteria kevalidan, kemenarikan, kepraktisan, dan keefektifan dalam pembelajaran. Kata kunci: pengembangan buku teks, kearifan lokal